Use of the empty chair in the Decentralized Autonomous Government of Machala-Ecuador, 2019-2020 - Argudo Herrera, Efraín (2021)
This article determines the scope, nature and evaluates the incidence of the empty chair citizen participation mechanism and its implementation by the decentralized autonomous government (GAD) of Machala. The timeframe comprises mayor Dario Macas’ administration from May 2019 to September 2020. For this purpose, we collected the minutes and municipal resolutions of the 2019-2020 period and surveyed citizens to know their perception of the soundness of this right. In this period, the occupation of the empty chair was acceptable in 74% of all sessions; however, this data does not agree with the results of further surveys as only 6% of subjects said they knew this right, while 17% have only a vague perception that it exists. Moreover, the representative of the empty chair made few interventions during the sessions and voted only randomly. This article makes recommendations, among them, that the GAD of Machala should fully satisfy and publicize the participation rights of all citizens.